Consciousness : creeping up on the hard problem - Gray, Jeffrey Alan (Oxford ; New York : Oxford University Press, 2004)
"How does conscious experience arise out of the functioning of the human brain? How is it related to the behaviour that it accompanies? How does the perceived world relate to the real world? Between them, these three questions constitute what is commonly known as the Hard Problem of consciousness. Despite vast knowledge of the relationship between brain and behaviour, and rapid advances in our knowledge of how brain activity correlates with conscious experience, the answers to all three questions remain controversial, even mysterious. This new book analyses these core issues and reviews the evidence from both introspection and experiment."--Jacket
Ch. 1. Stances towards the problem of consciousness -- Ch. 2. The illusory narrative of consciousness -- Ch. 3. Where science and consciousness meet -- Ch. 4. Intentionality -- Ch. 5. Reality and illusion -- Ch. 6. Enter qualia -- Ch. 7. A survival value for consciousness? -- Ch. 8. Creeping up on the hard problem -- Ch. 9. Epiphenomenalism revisted -- Ch. 10. Scrutinising functionalism -- Ch. 11. From Cartesian theatre to global workspace -- Ch. 12. The global neuronal workspace -- Ch. 13. The neural correlate of consciousness -- Ch. 14. Bottom-up vs. top-down processing -- Ch. 15. Egocentric space and the parietal lobes -- Ch. 16. Taking physics seriously -- Ch. 17. Consciousness of self : the point of view
Includes bibliographical references and index
Keywords: Consciousness; Neuropsychology; Consciousness -- physiology; Neuropsychology; Perception -- physiology; Consciousness